A rare differential for multiple café-au-lait macules: primary microcephaly-3 caused by recessive mutations in CDK5RAP2. Case report and literature review. - Finnegan, P.; Bourke, J.; O’Connor, C. (European Journal of Pediatric Dermatology, 2023)
Primary microcephaly-3 is an inherited disease transmitted with an autosomal recessive trait. Microcephaly is associated with multisystem malformations of variable severity that require a multidisciplinary assessment. The dermatologist intervenes to evaluate the café au lait spots and other associated skin dyschromias. A case of MCPH3 was reported and a review of the literature cases was performed, with reference to its dermatological manifestations.